PERIOD CHANGES IN CEPHEIDS BELONGING TO OPEN CLUSTERS AND ASSOCIATIONS - Berdnikov, L. N.; Glushkova, E. V.; Turner, D. G. (Одеські астрономічні публікації, 2017)
Cepheids belonging to open clusters and associations exhibit identical characteristics to field Cepheids in terms of their period changes.